Conservation agriculture: A manual for farmers and extension workers in Africa - Technical Centre for Agricultural and Rural Cooperation; International Institute of Rural Reconstruction (International Institute of Rural Reconstruction, 2009)
Based on the concept of integrating agricultural production practices with resource conservation measures, conservation agriculture holds great potential for Africa, where farmers are faced with low yields, poor soils, lack of capital and labour shortages. Illustrated with many line drawings, this manual draws on the skills and experience of 90 farmers, extension personnel and scientists from 16 African countries.